Testing Sunflower Inbred Lines for Tolerance to Phoma Black Stem - Dedić, Boško (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2013)
Phoma black stem is caused by a widespread pathogen Phoma macdonaldii Boerema. The disease occurs regularly, causing damage by early defoliation and premature ripening. Complete resistance of sunflower to this disease has never been found, but there are reports of differences in response by different genotypes. Fifty-four new inbred lines were tested in  our trials conducted at the Rimski Šančevi experimental field. Plants in one trial were non-irrigated, and irrigated in another. Sunflower plants were artificially inoculated with mycelial plugs in the bud stage. The length of stem lesions was measured and compared using an analysis of variance. Disease intensity was generally more severe in the non-irrigated field. There were significant differences in tolerance to Phoma black stem among the tested lines in both trials. The percentage of tolerant genotypes was 1.8%.
Keywords: Phoma macdonaldii; Sunflower; Tolerance; Inbred lines